Antioxidant properties of brazilian tropical fruits by correlation between different assays - Gregoris, Elena; Pereira Lima, Giuseppina Pace [UNESP]; Fabris, Sabrina; Bertelle, Mariangela; Sicari, Michela; Stevanato, Roberto (Hindawi, 2013)
Four different assays (the Folin-Ciocalteu, DPPH, enzymatic method, and inhibitory activity on lipid peroxidation) based on radically different physicochemical principles and normally used to determine the antioxidant activity of food have been confronted and utilized to investigate the antioxidant activity of fruits originated from Brazil, with particular attention to more exotic and less-studied species (jurubeba, Solanum paniculatum; pequi, Caryocar brasiliense; pitaya, Hylocereus undatus; siriguela, Spondias purpurea; umbu, Spondias tuberosa) in order to (i) verify the correlations between results obtained by the different assays, with the final purpose to obtain more reliable results avoiding possible measuring-method linked mistakes and (ii) individuate the more active fruit species. As expected, the different methods give different responses, depending on the specific assay reaction. Anyhow all results indicate high antioxidant properties for siriguela and jurubeba and poor values for pitaya, umbu, and pequi. Considering that no marked difference of ascorbic acid content has been detected among the different fruits, experimental data suggest that antioxidant activities of the investigated Brazilian fruits are poorly correlated with this molecule, principally depending on their total polyphenolic content. © 2013 Elena Gregoris et al.